Inteligencia artificial y los entornos personales de aprendizaje: atentos al uso adecuado de los recursos tecnológicos de los estudiantes universitarios - Castillejos López, Berenice (2022)
Artificial intelligence (AI) has invaded learning spaces seeking to revolutionize education. Content creators on social networks like TikTok share hacks or academic tricks to facilitate the development of student tasks, but sometimes what they share are nothing more than tools of unethical practices that are used in the deliverables that the teacher programs. Therefore, the purpose of this essay is to reflect on the impact that artificial intelligence generates in the personal learning environments of university centenarians from academic hacks and tools to carry out unethical practices in the classroom. As a conclusion, it is obtained that the critical and creative thinking of the linguistic and logical-mathematical intelligence are affected when the student applies this type of tools. A problem of human values in the apprentice is identified.